ANALISIS YURIDIS TERHADAP PERBUATAN MELAWAN HUKUM DALAM SENGKETA HAK PEKERJA MELALUI PUTUSAN NOMOR 287/PDT.G/2024/PN MDN - Ira Safitri; Muhammad Yoga Pratama; Filzah Irshadi; Putri Juliani Br Tarigan; Salwa Sabrina; Parlaungan Gabriel Siahaan (TAHKIM, 2024)
This research examines the decision of the Medan District Court regarding the issue of unlawful acts committed by PT. Mandiri Tunas Finance in connection with termination of employment and uncertainty in payment of workers' rights. This problem highlights serious problems in the implementation of court decisions in Indonesia, especially in industrial relations, where legal decisions are often ignored. This research emphasizes the importance of enforcing court decisions to ensure justice and legal certainty in the Indonesian civil law system. The method used in this research is normative juridical. The discussion in this research shows two things, namely: the impact of PT non-compliance. Mandiri Tunas Finance regarding termination of employment and uncertainty in payment of workers' rights and emphasizes the importance of enforcing court decisions in the civil law system in Indonesia. This research concludes that PT. Mandiri Tunas Finance's response to the Medan District Court's decision highlights the need for consistent enforcement of civil law. Failure to pay workers their rights harms them and reduces public trust in the legal system. To prevent similar cases, it is important to ensure good implementation of court decisions to guarantee legal certainty, justice, public safety, and encourage legal development. Keywords: Workers' Rights, Unlawful Actions, Court Decisions